Pragmatic communication abilities in children and adults: implications for rehabilitation professionals. Issue 18 (28th August 2017) - Turkstra, Lyn S.; Clark, Allison; Burgess, Sloane; Hengst, Julie A.; Wertheimer, Jeffrey C.; Paul, Diane
Abstract: Purpose : The purpose of this study is to provide a review of pragmatic communication ability and its disorders, as a resource for rehabilitation team members. This review is a product of the Joint Committee on Interprofessional Relations Between the American Speech-Language-Hearing Association and Division 40: Society for Clinical Neuropsychology of the American Psychological Association. Method : Review of the literature and expert opinion. Results : We summarize key theoretical frameworks that guide assessment of pragmatic communication ability, describe the developmental progression of pragmatic skills and expectations for children and adults, provide an overview of pragmatic communication disorders, and discuss current assessment approaches. Conclusions : An understanding of pragmatic communication disorders may assist all rehabilitation team members, as impairments in this domain may have significant effects on rehabilitation progress and outcomes. Implications for Rehabilitation: Pragmatic communication ability is the ability to use language in context, beyond understanding and expressing basic word meanings (semantics) in the correct grammatical forms (syntax). Pragmatic communication deficits have been documented in many of the populations frequently referred for rehabilitation, and can affect both progress during rehabilitation and outcomes from treatment. A broader understanding of pragmatic communication functions can help team members identify a patient's strengths and limitations, inform treatment planning, and improve communication among healthcare professionals, thereby contributing to improved outcomes for patients and their families.